Urgensi Penguatan Kedudukan Dispute Board guna Menjamin Kepastian Hukum Proyek Jalan Multi-Tahun - Paksi Aan Syuryadi; Muhtadi Muhtadi; Kasmawati Kasmawati (Mahesa Research Center, 2026)
Multi-year infrastructure projects are inherently characterized by high legal and financial complexities, where conventional litigation and post-project arbitration often prove to be protracted, reactive, and deleterious to project continuity. While the Indonesian regulatory framework, specifically Government Regulation No. 22 of 2020, has formally recognized the Dispute Board (DB) mechanism, its practical efficacy remains constrained by a profound normative lacuna regarding executorial enforceability. This research employs a legal-doctrinal method with a comparative approach, analyzing the Indonesian landscape against the FIDIC international standards and the Statutory Adjudication models of the United Kingdom and Singapore. The findings elucidate a critical